Evaluation of the effect of obesity on fibromyalgia in premenopausal female patients - Dicle Aydogdu Oguz; Mujgan Gurler (Medicine Science, 2022)
Obesity is a chronic disease whose prevalence is increasing all over the world. The relationship between obesity and some rheumatic diseases such as Fibromyalgia Syndrome (FMS) has recently attracted attention. In this study, we investigated the effect of obesity on FMS in premenopausal female patients. Anamnesis, physical examination and laboratory data obtained from 103 female patients who were divided into two groups as obese and non-obese according to body mass index (BMI) were statistically analyzed in terms of FMS. 25.2% of the women participating in the study were diagnosed with FMS, and the mean age of the cases was 33.42 (± 10.41), the mean weight was 79.65 (± 19.91), and the mean BMI was 30.52 (± 7.75). The mean age of the obese was higher 38.48 (± 8.95) and the incidence of obesity was significantly higher with age (p ˂ 0.001). The frequency of FMS (p = 0.001), Fibromyalgia Impact Questionnaire results (p = 0.001) and tender point numbers in the Widespread Pain Index Scale (p ˂ 0.001) were significantly higher in the obese group. There was no statistically significant difference between the obese and non-obese groups in terms of marital status, occupation, smoking history and education levels. Obesity prevalence is increasing all over the world and the results of the present study reveal FMS complications are getting worse by obesity. Therefore, prevention and medical treatment of obesity, can positively affect many parameters in the body and reduce the incidence of FMS. [Med-Science 2022; 11(1.000): 387-93]